2021
DOI: 10.1002/sctm.20-0385
|View full text |Cite
|
Sign up to set email alerts
|

Human mesenchymal stromal cells do not express ACE2 and TMPRSS2 and are not permissive to SARS-CoV-2 infection

Abstract: Anti‐inflammatory and immune‐modulatory therapies have been proposed for the treatment of COVID‐19 and its most serious complications. Among others, the use of mesenchymal stromal cells (MSCs) is under investigation given their well‐documented anti‐inflammatory and immunomodulatory properties. However, some critical issues regarding the possibility that MSCs could be infected by the virus have been raised. Angiotensin‐converting enzyme 2 (ACE2) and type II transmembrane serine protease (TMPRSS2) are the main h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 25 publications
7
35
0
Order By: Relevance
“…By having used hUC-MSC lots derived from multiple donors, we have established that there is no ACE2 expression in hUC-MSCs, while TMPRSS2 expression could be donor-dependent. This provides a reasonable basis to support the evasion of infection by hUC-MSCs, making them an effective, non-vector, option for COVID-19 treatment, thereby supporting the findings of Avanzini et al [ 53 ] and Leng et al [ 32 ].…”
Section: Discussionsupporting
confidence: 81%
“…By having used hUC-MSC lots derived from multiple donors, we have established that there is no ACE2 expression in hUC-MSCs, while TMPRSS2 expression could be donor-dependent. This provides a reasonable basis to support the evasion of infection by hUC-MSCs, making them an effective, non-vector, option for COVID-19 treatment, thereby supporting the findings of Avanzini et al [ 53 ] and Leng et al [ 32 ].…”
Section: Discussionsupporting
confidence: 81%
“…In parallel with proper ventilation management, dexamethasone, antiviral agents, convalescent plasma, and IL-1/6 inhibitors, MSCs are also considered a promising candidate therapy for COVID-19-related ARDS (4,119). It was reported that MSCs from the bone marrow, amniotic fluid, and adipose tissue were all resistant to SARS-CoV-2 infection due to the low expressions of angiotensin-converting enzyme 2 (ACE-2) and transmembrane protease serine subtype 2 (TMPRSS2) on the cell surface under both steady-state and inflammatory conditions (120,121), which supported the potential applicability of MSCs for COVID-19 treatment (Figure 1).…”
Section: Mscs In Covid-19-related Ardsmentioning
confidence: 99%
“…Noteworthy, another advantage of MSCs is that they do not express the ACE-2 receptor and the priming enzyme that allow SARS-CoV-2 engagement and entry [ 118 ]. Cultured MSCs from different tissues were exposed to SARS-CoV-2 wild strain without evidence of cytopathic effects; moreover, under in vitro challenges with the virus, the conditioned medium did not contain viral particles [ 118 ].…”
Section: Inflammation and Immune Responsementioning
confidence: 99%
“…Noteworthy, another advantage of MSCs is that they do not express the ACE-2 receptor and the priming enzyme that allow SARS-CoV-2 engagement and entry [ 118 ]. Cultured MSCs from different tissues were exposed to SARS-CoV-2 wild strain without evidence of cytopathic effects; moreover, under in vitro challenges with the virus, the conditioned medium did not contain viral particles [ 118 ]. The lack of ACE2 and TMPRSS expression was also interpreted as a key element for the reported clinical success of an MSC therapy trial, described in more detail below, in seven patients with COVID-19 pneumonia [ 119 ].…”
Section: Inflammation and Immune Responsementioning
confidence: 99%